2019
DOI: 10.1002/cne.24732
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of opsins in the eye photoreceptor cells of the terrestrial slug Limax valentianus

Abstract: Visual opsins coupled with Gq‐type G protein have been considered to be responsible for the vision in mollusks. Recent transcriptomic studies, however, revealed the presence of opsin mRNA belonging to different groups of opsin subfamilies in the eyes of mollusks. In the present study, we found that at least three different opsins, Gq‐coupled rhodopsin, opsin5A, and xenopsin, are co‐expressed in the rhabdomeric photoreceptor cell in the eyes of the terrestrial slug Limax valentianus. These opsins were all local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 51 publications
5
22
1
Order By: Relevance
“…We detected all five mRNA species in the ST and three mRNA species in the brain (Opn5A, retinochrome and xenopsin; Fig. 4A), replicating previous findings (Matsuo et al, 2019). The expression of xenopsin mRNA was also detected in the BW and the PS, whereas retinochrome was barely detected in the BW and was not found in the PS (Fig.…”
Section: Expression Of Opsin Mrnasupporting
confidence: 90%
See 4 more Smart Citations
“…We detected all five mRNA species in the ST and three mRNA species in the brain (Opn5A, retinochrome and xenopsin; Fig. 4A), replicating previous findings (Matsuo et al, 2019). The expression of xenopsin mRNA was also detected in the BW and the PS, whereas retinochrome was barely detected in the BW and was not found in the PS (Fig.…”
Section: Expression Of Opsin Mrnasupporting
confidence: 90%
“…However, a larger percentage of animals was expected to avoid short-wavelength light if monochromatic light with an equivalent photon flux density was used instead. We and other groups also demonstrated that the eye of Limax is more responsive to short-wavelength blue light, especially when the eye is light adapted (Suzuki et al, 1979;Matsuo et al, 2017Matsuo et al, , 2019. The preferential use of short-wavelength light is thought to be a widely conserved phenomenon in the animal kingdom (Gehring and Rosbash, 2003;Erren et al, 2008), and the slugs also appear to have inherited this trait.…”
Section: ) Andsupporting
confidence: 54%
See 3 more Smart Citations